2014
DOI: 10.1007/jhep11(2014)157
|View full text |Cite
|
Sign up to set email alerts
|

On the relevance of the thermal scalar

Abstract: We discuss near-Hagedorn string thermodynamics in general spacetimes using the formalism of the thermal scalar. Building upon earlier work by Horowitz and Polchinski, we relate several properties of the thermal scalar field theory (i.e. the stress tensor and U(1) charge) to properties of the highly excited or near-Hagedorn string gas. We apply the formulas on several examples. We find the pressureless near-Hagedorn string gas in flat space and a non-vanishing (angular) string charge in AdS 3 . We also find the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…Our goal is to use this continuation of the cigar CFT to tell us something about the continuation for the flat cones. 21 It seems difficult to make this point more firmly: the full stress tensor of the string gas seems difficult to obtain; we only obtained the most dominant contribution in [57]. The free energy however is directly linked to the canonical internal energy which is to be interpreted as the spatial integral of T 0 0 and the result we obtain is then only in the weaker integrated sense.…”
Section: Continuation Of the Flat Orbifold Inherited From The Cigar Omentioning
confidence: 75%
“…Our goal is to use this continuation of the cigar CFT to tell us something about the continuation for the flat cones. 21 It seems difficult to make this point more firmly: the full stress tensor of the string gas seems difficult to obtain; we only obtained the most dominant contribution in [57]. The free energy however is directly linked to the canonical internal energy which is to be interpreted as the spatial integral of T 0 0 and the result we obtain is then only in the weaker integrated sense.…”
Section: Continuation Of the Flat Orbifold Inherited From The Cigar Omentioning
confidence: 75%
“…In the microcanonical ensemble, the dominant contribution at very high energy E of the energy density ε(ρ) and radial pressure p(ρ) of the string gas are given by [5] ε(ρ) = 2 E Aaα…”
Section: The Thermal Scalar In Rindler Spacementioning
confidence: 99%
“…Let us now consider a long string gas in the microcanonical ensemble with energy E. In [26,30] it was shown that the average value of the Euclidean energy-momentum tensor at high energy is given by the energy-momentum tensor of the thermal scalar field theory, evaluated on the zero-mode:…”
Section: Jhep02(2016)041mentioning
confidence: 99%
“…The origin of the pressure however is not kinetic but entropic. As one can check [30], a microcanonical ensemble describing a long string gas with energy E at infinity (which means ρ = 1/a where the temperature equals 1/β):…”
Section: Jhep02(2016)041mentioning
confidence: 99%